Strategies and interventions for healthy adolescent growth, nutrition, and development. Issue 10320 (8th January 2022) - Hargreaves, Dougal; Mates, Emily; Menon, Purnima; Alderman, Harold; Devakumar, Delan; Fawzi, Wafai; Greenfield, Geva; Hammoudeh, Weeam; He, Shanshan; Lahiri, Anwesha; Liu, Zheng; Nguyen, Phuong Hong; et al.
Summary: Adolescence is a pivotal point in the life course, characterised by transformative physical, cognitive, and emotional growth, an openness to change, and a drive to reshape the social environment. It offers unique opportunities to adopt changes in diet and physical activity that can persist into later life. Yet pre-existing nutritional problems, including micronutrient deficiencies, food insecurity, and poor-quality diets, persist at the same time as adolescents face the rapid emergence of an obesity epidemic. Adolescent growth and nutrition has been largely overlooked in intervention and policy research. Most intervention studies have emphasised micronutrient supplementation, with few taking into account the multiple drivers of adolescent diets. This Series paper highlights that effective interventions and policies will need to cut across sectors; be supported by multifaceted and multilevel policy; and extend across education, health, food systems, social protection, and digital media. Better data standardisation and systems will be essential in coordinating and monitoring these responses. In a context of shifts in planetary ecosystems and commercial drivers, resilient food systems will need to both ensure access to healthy and affordable foods and provide the infrastructure and incentives for continuing physical activity. Intergenerational partnerships with young people will be essential in bringing about transformative change and ensuring that food policies reflect their needs and aspirations.